Commonalities between the Atacama Desert and Antarctica rhizosphere microbial communities - Contreras, María José; Leal, Karla; Bruna, Pablo; Nuñez-Montero, Kattia; Goméz-Espinoza, Olman; Santos, Andrés; Bravo, León; Valenzuela, Bernardita; Solis, Francisco; Gahona, Giovanni; Cayo, Mayra; Dinamarca, M. Alejandro; et al. (Frontiers in Microbiology, 2023)
Plant-microbiota interactions have significant effects on plant growth, health, and productivity. Rhizosphere microorganisms are involved in processes that promote physiological responses to biotic and abiotic stresses in plants. In recent years, the interest in microorganisms to improve plant productivity has increased, mainly aiming to find promising strains to overcome the impact of climate change on crops. In this work, we hypothesize that given the desertic environment of the Antarctic and the Atacama Desert, different plant species inhabiting these areas might share microbial taxa with functions associated with desiccation and drought stress tolerance. Therefore, in this study, we described and compared the composition of the rhizobacterial community associated with Deschampsia antarctica (Da), Colobanthus quitensis (Cq) from Antarctic territories, and Croton chilensis (Cc), Eulychnia iquiquensis (Ei) and Nicotiana solanifolia (Ns) from coastal Atacama Desert environments by using 16S rRNA amplicon sequencing. In addition, we evaluated the putative functions of that rhizobacterial community that are likely involved in nutrient acquisition and stress tolerance of these plants. Even though each plant microbial rhizosphere presents a unique taxonomic pattern of 3019 different sequences, the distribution at the genus level showed a core microbiome with a higher abundance of Haliangium, Bryobacter, Bacillus, MND1 from the Nitrosomonadaceae family, and unclassified taxa from Gemmatiamonadaceae and Chitinophagaceae families in the rhizosphere of all samples analyzed (781 unique sequences). In addition, species Gemmatirosa kalamazoonesis and Solibacter usitatus were shared by the core microbiome of both Antarctic and Desert plants. All the Running Title 16 \* Arabic \* MERGEFORMAT 4 taxa mentioned above had been previously associated with beneficial effects in plants. Also, this microbial core composition converged with the functional prediction related to survival under harsh conditions, including chemoheterotrophy, ureolysis, phototrophy, nitrogen fixation, and chitinolysis. Therefore, this study provides relevant information for the exploration of rhizospheric microorganisms from plants in extreme conditions of the Atacama Desert and Antarctic as promising plant growthpromoting rhizobacteria.